Germination of Salsoa vermiculata seeds as affected by temperature and storage duration - Homrani Bakali A.; Acherchouk M.; Maatougui A.; Mrabet R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Salsola vermiculata L. Syn. Caroxylon villosum (Delile) Akhani & Roalson (Chenopodiaceae) is a perennial small woody species widely distributed in arid zones of Middle East and North Africa (MENA) region. It is one of the promising pastoral species for the rehabilitation of arid rangelands in Mororcco. The objectives of this study were to determine the effects of temperature and duration of seed storage on the germination of Caroxylon villosum (Salsola vermiculata var villosa). Experiments were conducted in the laboratory of the Experimental station of Errachidia (Morocco). Seeds were germinated at six alternating temperatures (10 – 0, 5 – 15, 10–20, 15–25, 20–30 and 25 – 40 °C) with 14-8 h photoperiod and six cardinal temperatures (5, 15, 20, 25, 30 and 40 °C). Three storage durations of seeds under ambient conditions (seed of the same year of production, 2 years storage and 4 years storage) were tested. Germination percentage and germination rate were high for several regime of temperature except for higher temperatures. In addition, germination decreases significantly with the duration of seed storage.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)